Modern personal radio systems - Macario, R. C. V. (Raymond Charles Vincent) (Institution of Electrical Engineers, 1996)
This topical new book builds upon an earlier IEE text Personal & mobile radio systems, by the same editor, which set out the fundamental issues in a discipline that appeared to have global expansion potential. That potential has now become a reality, and something more than a new edition of the previous book was needed to bring it up to date. This book is completely new, drawing on the experience and the many intensive studies that have been concentrated in this field in the past five years. The book gives a clear and detailed insight into the fundamental problems and solutions found in modern personal communications: service requirements, coverage problems, multipath interference, cellular architectures and signalling, network management, data and supplementary services, satellite services. In particular it describes the approach of the GSM methodology, as one of the most intensively developed standards, to some of these problems, although the same principles also apply to DCS 1800 and other technologies.